2016
DOI: 10.1002/ecm.1228
|View full text |Cite
|
Sign up to set email alerts
|

The effect of demographic correlations on the stochastic population dynamics of perennial plants

Abstract: Understanding the influence of environmental variability on population dynamics is a fundamental goal of ecology. Theory suggests that, for populations in variable environments, temporal correlations between demographic vital rates (e.g., growth, survival, reproduction) can increase (if positive) or decrease (if negative) the variability of year-to-year population growth. Because this variability generally decreases long-term population viability, vital rate correlations may importantly affect population dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 77 publications
5
54
0
1
Order By: Relevance
“…While we saw statistical evidence for both patterns, we did not find any strong effect of these mechanisms on population growth rates. Some other studies have found potentially significant effects of demographic rate buffering on extinction risk (Garcia 2003, McDonald et al 2016), while others have not (Compagnoni et al 2016). In part, our negative result may be due to the very limited data we have with which to evaluate these effects; with only four annual transitions of data, characterizing the pattern of elasticity vs. variation of vital rates, or the covariance of different rates, is difficult.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…While we saw statistical evidence for both patterns, we did not find any strong effect of these mechanisms on population growth rates. Some other studies have found potentially significant effects of demographic rate buffering on extinction risk (Garcia 2003, McDonald et al 2016), while others have not (Compagnoni et al 2016). In part, our negative result may be due to the very limited data we have with which to evaluate these effects; with only four annual transitions of data, characterizing the pattern of elasticity vs. variation of vital rates, or the covariance of different rates, is difficult.…”
Section: Discussionmentioning
confidence: 98%
“…), while others have not (Compagnoni et al. ). In part, our negative result may be due to the very limited data we have with which to evaluate these effects; with only four annual transitions of data, characterizing the pattern of elasticity vs. variation of vital rates, or the covariance of different rates, is difficult.…”
Section: Discussionmentioning
confidence: 98%
“…Methods for vital rate estimation and population modelling closely followed our previous study (Compagnoni et al, ). We used the long‐term demographic data to fit statistical models for six individual‐level processes ("vital rates") that collectively determined population dynamics: (a) survival, (b) growth, (c) flowering (yes or no), (d) fertility of flowering plants (total # flowering stalks), (e) flower stalk abortion rate (flower viability), and (f) seedling recruitment (detailed methods are available in Appendix ).…”
Section: Methodsmentioning
confidence: 99%
“…Methods for vital rate estimation and population modelling closely followed our previous study (Compagnoni et al, 2016). We used the long-term demographic data to fit statistical models for six in- (detailed methods are available in Appendix S1).…”
Section: Vital Rate Estimationmentioning
confidence: 99%
“…For plants, such models can be particularly powerful tools for assessing population viability or recovery in highly variable environments (cf. Tuljapurkar 1990, Caswell 2000, Caswell and Kaye 2001, Tuljapurkar et al 2003, Koons et al 2005, Boyce 2006, Buckley et al 2010, Ellis and Crone 2013, Davison et al 2013, Compagnoni et al 2016, McDonald et al 2016, Needham et al 2018 and references therein).…”
Section: Introductionmentioning
confidence: 99%